Hubungan Hardiness Dengan Academic Resilience Pada Mahasiswa Fakultas Psikologi Yang Berkuliah Sambil Bekerja Di Universitas Prima Indonesia - Clarissa Lawrence; Korina Korina; Achmad Irvan Dwi Putra; Winida Marpaung (Jayapangus Press, 2026)
This study aims to analyze the relationship between hardiness and academic resilience in Psychology students at Prima Indonesia University who are studying while working. Hardiness and academic resilience are understood as two important constructs that influence students' ability to maintain academic performance amidst dual demands. This study uses a quantitative method by examining the relationship between hardiness and academic resilience in a group of working students who are rarely studied in Indonesian educational psychology. This study involved 258 respondents identified through Isaac Michael Tables from a population of 976 students. Data were collected through questionnaires and analyzed using Pearson Product Moment correlation using SPSS Version 27 software. The results of the analysis showed a positive and significant relationship between hardiness and academic resilience (r = 0.212; p = 0.000). This finding confirms that hardiness plays a role as a psychological factor that contributes to the academic resilience of working students, and fills the gap in research on these two variables in the segment of students with dual burdens in the context of higher education in Indonesia.